Nickel-mediated polyol synthesis of hierarchical V2O5 hollow microspheres with enhanced lithium storage properties. Issue 5 (8th December 2014) - Zheng, Yan-Zhen; Ding, Haiyang; Uchaker, Evan; Tao, Xia; Chen, Jian-Feng; Zhang, Qifeng; Cao, Guozhong
Abstract : Hierarchical Ni–V2 O5 hollow microspheres, prepared via a template-free Ni-mediated polyol process, have excellent Li storage properties as a Li-ion battery cathode (high capacity (294 mA h g −1 ), superior cycling stability/rate performance) due to their unique structure and low V valence state. Abstract : In this study, a facile template-free synthesis of hierarchical V2 O5 hollow microspheres has been developed, based on a nickel-mediated polyol process and subsequent calcinations. It is found that morphological control over V2 O5 micro-architecture is realized by adding Ni into the polyol process. XPS results demonstrate that Ni doping promotes the formation of low valence state vanadium in V2 O5 samples and is beneficial to maintain electric stability to the V 4+ state. Due to unique structure and low valence state vanadium in Ni–V2 O5 microspheres, Ni (10 mol%)–V2 O5 used as the cathode material for a lithium ion battery exhibits excellent lithium storage properties with very high capacity (294 mA h g −1 ) and superior cycling stability and rate performance. The good electrochemical performance suggests that this hierarchical Ni–V2 O5 material could be a promising candidate as a cathode material for lithium-ion batteries.